Silymarin protects plasma membrane and acrosome integrity in sperm treated with sodium arsenite - Farzaneh Eskandari; Hamid Reza Momeni (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2016)
Background: Exposure to arsenic is associated with impairment of male reproductive function by inducing oxidative stress. Silymarin with an antioxidant property scavenges free radicals. Objective: The aim of this study was to investigate if silymarin can prevent the adverse effects of sodium arsenite on ram sperm plasma membrane and acrosome integrity. Materials and Methods: Ram epidydimal spermatozoa were divided into five groups: spermatozoa at 0 hr, spermatozoa at 180 min (control), spermatozoa treated with silymarin (20 μM) + sodium arsenite (10 μM) for 180 min, spermatozoa treated with sodium arsenite (10 μM) for 180 min and spermatozoa treated with silymarin (20 μM) for 180 min. Double staining of Hoechst and propidium iodide was performed to evaluate sperm plasma membrane integrity, whereas comassie brilliant blue staining was used to assess acrosome integrity. Results: Plasma membrane (p< 0.001) and acrosome integrity (p< 0.05) of the spermatozoa were significantly reduced in sodium arsenite group compared to the control. In silymarin + sodium arsenite group, silymarin was able to significantly (p< 0.001) ameliorate the adverse effects of sodium arsenite on these sperm parameters compared to sodium arsenite group. The incubation of sperm for 180 min (control group) showed a significant (p< 0.001) decrease in acrosome integrity compared to the spermatozoa at 0 hour. The application of silymarin alone for 180 min could also significantly (p< 0.05) increase sperm acrosome integrity compared to the control. Conclusion: Silymarin as a potent antioxidant could compensate the adverse effects of sodium arsenite on the ram sperm plasma membrane and acrosome integrity.